2018
DOI: 10.1007/s10147-017-1233-8
|View full text |Cite
|
Sign up to set email alerts
|

The clinical features of squamous cell lung carcinoma with sensitive EGFR mutations

Abstract: The administration of afatinib to Sq patients after selecting patients using the EGFR mutation test based on their underlying pulmonary disease and smoking status would likely result in a population with a greater sensitivity to afatinib.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Data from these clinical trials demonstrated that as a maintenance treatment option, the therapeutic effects of erlotinib were similar to those of first- or second-line chemotherapy. Furthermore, the role of afatinib in the treatment of LSCC has been evaluated in several clinical trials 39. Shun Lu and his colleagues conducted a post hoc analysis of the data of patients in the LUX-Lung 8 trial conducted in mainland China 23.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from these clinical trials demonstrated that as a maintenance treatment option, the therapeutic effects of erlotinib were similar to those of first- or second-line chemotherapy. Furthermore, the role of afatinib in the treatment of LSCC has been evaluated in several clinical trials 39. Shun Lu and his colleagues conducted a post hoc analysis of the data of patients in the LUX-Lung 8 trial conducted in mainland China 23.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with erlotinib, afatinib reduced the risk of disease progression or death in the Chinese subgroup by 30% (HR, = 0.70; 95% CI, 0.38–1.27), thereby indicating that afatinib may be considered as a feasible treatment option for Chinese patients with advanced LSCC following the progression of the disease after platinum-based chemotherapy. Yuri Taniguchi and his colleagues showed that the administration of afatinib to LSCC patients who were selected using the EGFR mutation test based on the underlying pulmonary disease and smoking status would likely result in a population with a greater sensitivity to afatinib 39…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a study has shown afatinib to be more effective than erlotinib as a second-line treatment for patients with advanced SCC (15). Furthermore, a study retrospectively reviewing patients with EGFR -mutated squamous cell carcinoma treated with EGFR -TKIs as first-line therapies revealed that afatinib was effective in two of two cases, while gefitinib was not effective in two of two cases (16). From these and the present case findings, we suggest that afatinib can be considered as a treatment option for EGFR -mutated tumors undergoing SCC transformation, particularly those without T790M mutation.…”
Section: Discussionmentioning
confidence: 99%
“…So most patients with lung SCC have no chance to get benefit from EGFR tyrosine-kinase inhibitors (TKIs). However, it was found in the subgroup analysis of several studies that among all lung SCC patients, the EGFR mutation rate in female patients seemed to be higher, about 14.4% to 33.3% (6,10,11,14). But the sample size of female SCC in these studies were very small, and at present there was no specific study on EGFR mutation status in female lung SCC.…”
Section: Introductionmentioning
confidence: 92%
“…Previous respective studies showed that lung SCC patients with sensitive EGFR mutations could obtain clinical benefits from EGFR-TKIs (9,13,24). While in a study of Turkish female lung SCC patients with EGFR positive mutation, the response to gefitinib was not good (14). Therefore, the efficacy of EGFR-TKIs for female lung SCC patients with sensitive EGFR mutations remains unclear.…”
Section: Introductionmentioning
confidence: 99%